Stephania Padovani - Spinillo, Carla (InfoDesign, 2008)
<img title="id_v5_n1_2008_61_64_spinillo_230" src="http://www.infodesign.org.br/revista/public/site/images/fnunes/id_v5_n1_2008_61_64_spinillo_230.jpg" alt="id_v5_n1_2008_61_64_spinillo_230" width="196" height="230" /> Stephania Padovani has a Ph.D. in Cognitive Ergonomics from Loughborough University (2001); she is a graduate of ESDI /UERJ (1996) and has a Master´s Degree in Design from PUC-Rio (1998). She is currently a professor of the Master´s Degree program in Design at UFPR and vice-coordinator of the undergraduate course in Design. She holds a Research Productivity grant from CNPq (PQ2) and her main fields of interest are Human-Computer Interaction and Usability, with emphasis on Information Design and Ergonomics. Stephania provides opinions for several national and international design events and her work has been published in renowned periodicals such as the International Journal of Human-Computer Studies, Revista Estudos em Design and Design em Foco. She is also a member of the board of the Brazilian Society of Information Design (SBDI - Sociedade Brasileira de Design da Informação) and of the InfoDesign editorial body.